Occupational Health and Safety in Ethiopia: A review of Situational Analysis and Needs Assessment - Kumie, Abera (Ethiop J Health Dev, 2016)
BACKGROUND: The current rapid economic development has brought changes in workplaces in developing countries, including Ethiopia. The organization of occupational health and safety services is not yet resilient enough to handle the growing demands for workers’ health in the context of industrialization. There is limited information on the gaps and needs of occupational health services in workplaces in Ethiopia. OBJECTIVES: The present review article describes the existing profile of occupational safety and health services in Ethiopia and identifies the current gaps and needs in the services. METHODS: Secondary data sources were reviewed using a structured checklist to explore the status of occupational safety, health services and related morbidity. Local literature was consulted in order to describe the type and prevalence of work related hazards, patterns of industries and of workforce. Published articles were searched in Google, Google scholar, PUBMED, and HINARI databases. Relevant heads of stakeholder organizations and experts were interviewed to verify the gaps that were synthesized using desk review. RESULTS: Ethiopia is an agrarian country that is industrializing rapidly with a focus on construction, manufacturing, mining, and road infrastructure. An estimated work force of about two million is currently engaged in the public and private sectors. Males constitute the majority of this workforce. Most of the workforce has basic primary education. Commonly observed hazards in the workplace include occupational noise and dust of various types in manufacturing sectors and chemical exposures in the flower industry. Injury in both the agriculture and the manufacturing sectors is another workplace hazard commonly observed in the country. A lack of information made assessing workplace exposures in detail difficult. The prevalence of noise exposure was found to be high with the potential to seriously impact hearing capacity. Exposure to dust in textile and cement factories greatly exceeded international permissible limits. There is a high level of workplace injuries that often leads to an extended loss of productive working days. Occupational safety and health services were found to be inadequately organized. There is limited practice in exposure assessment and monitoring. This happens to be true despite the existing favorable environment in areas of policies and regulations. CONCLUSION AND RECOMMENDATION: There is a severe scarcity of peer-reviewed literature related to workplace exposures and their impact on workplace health and safety. Limited adequately skilled manpower is available. The internal infrastructural capacity is weak and cannot help to identify and assess hazards in the workplace. Monitoring system and laboratory investigation is limited despite the presence of favorable policy and regulatory frameworks. Addressing these gaps is of immediate concern.